A practical guide to the invariant calculus - Mansfield, Elizabeth Louise (Cambridge monographs on applied and computational mathematics, 2010)
Explaining and developing new applications of continuous symmetry groups (Lie groups), in particular, the symbolic manipulation of invariants of group actions this text uses worked examples and exercises.